The Effect of Manager's Emotional Support and Procedural Justice on Employee Performance Mediated by Work Engagement PT. Nassaba Lacuna Brilliant Depok City - Mirza Zulmi; Besar Agung Martono (Yayasan Amerta Insan Unggul, 2025)
This study examines the influence of managerial emotional support and procedural justice on employee performance, with work engagement as a mediating variable at PT. Nassaba Lacuna Brilliant. The research was driven by concerns over declining employee performance due to lack of compliance, low involvement, and insufficient managerial support. Using a quantitative approach, data were collected via questionnaires employing a 1–10 Likert scale from employees selected with a 5% margin of error. The data were analyzed using multiple linear regression and hypothesis testing (t-test and F-test) with SPSS version 30. The results show that emotional support from managers significantly influences work engagement (β = 0.001), but does not directly or indirectly affect employee performance (direct β = 0.276; indirect β = 0.107). This suggests that emotional support alone is insufficient to enhance performance. In contrast, procedural justice significantly impacts both work engagement (β = 0.003) and employee performance, with a stronger direct effect (β = 0.380) compared to indirect (β = 0.092). However, work engagement does not significantly affect employee performance (β = 0.075) and thus does not function as a mediating variable. In conclusion, procedural justice directly enhances employee performance, while work engagement does not mediate the relationship in this model.